Bodies, mobilities and spaces in rosario’s recreational street - Roldán, Diego; Godoy, Sebastián (InMediaciones de la Comunicación, 2017)
In contemporary cities, the implementation certain types of devices is increasingly common, which, far from curtailing the mobility of their populations, incentivize certain repertories of body practices and direction vectors. This range of government technologies does not act directly upon individual bodies, but unfolds upon populations as a magnitude and urban environment as an ambient. In this paper, the development of a particular device will be analyzed, the Recreational Street en Rosario city, which seeks to promote a specific type of mobility (a pedestrian one, with the aim of recreation and moderate physical exercise), using certain arteries of the city as a circuit and the public space as scenery. Through the adaptation of a specific and artificial environment, the street funnels a range of practices of the population while powers the most valued urban public spaces. They function as a landscape for pedestrians in the service of the recreation, and promote the tourism image and overall design of the city. To understand its performance, a field work has been carried out which consist in qualitative observations added to the record of the experience of the body of researchers in the use of the street.